Odpowiedzi

2009-11-19T19:54:30+01:00
A) 3x-2y=0/*3
6y-10x=4

9x-6y=0
6y-10x=4

x=4
12-2y=0

x=4
y=-6 METODA PRZECIWNYCH WSPółCZYNNIKóW

1 5 1
2009-11-19T20:05:46+01:00
A) 3x-2y=0
6y-10x-4=0
3x-2y=0/*3
6y-10x-4=0
9x-6y=0
6y-10x=4
9x-6y-6y-10x=4
-x=4/:(-1)
x=-4
3x-2y=0
x=-4
3*(-4)-2y=0
x=-4
-12-2y=0
x=-4
-2y=12/:(-2)
y=-6
b) x(x+1)-(x+2)²=y-3
½x-¼y=4/*4
x²+x-x²-4x-4=y-3
2x-y=16
-3x+y=-3+4
2x-y=16
-3x+y=1
2x-y-3x+y=16+1
-x=17/:(-1)
x=-17
2x-y=16
x=-17
2*(-17)-y=16
x=-17
34-y=16
x=-17
-y=16-34
x=-17
-y=-18/:(-1)
x=-17
y=18
c) -x+2y=-3/*2
2x-4y=0
-2x+4y=-6
2x-4y=0
-2x+4y+2x-4y=-6
0≠-6
układ równań sprzeczny